Assessing measles vaccine failure in Tianjin, China. Issue 25 (31st May 2019) - Masters, Nina B.; Wagner, Abram L.; Ding, Yaxing; Zhang, Ying; Boulton, Matthew L.
Highlights: Measles cases among children in Tianjin still occur in those who have been vaccinated. 29% of measles surveillance system cases with known vaccine history were vaccinated. In a Case Series from 2011 to 2015, 54% of measles cases had been vaccinated. Incremental doses of measles vaccine increased the time-to-disease onset. More research is needed to understand the reasons for vaccine failure. Abstract: Despite increasing global measles vaccination coverage, progress toward measles elimination has slowed in recent years. In China, children receive a measles-containing vaccine (MCV) at 8 months, 18–24 months, and some urban areas offer a third dose at age 4–6 years. However, substantial measles cases in Tianjin, China, occur among individuals who have received multiple MCV doses. This study describes the vaccination history of measles cases 8 months – 19 years old. Data came from measles cases in Tianjin's reportable disease surveillance system (2009–2013), and from a case control study (2011–2015). Twenty-nine percent of those in the surveillance dataset and 54.4% of those in the case series received at least one dose of MCV. The minimum and median time-to-diagnosis since vaccination revealed an increase in time since vaccination for incremental doses. Considerable measles cases in Tianjin occur in vaccinated children, and further research is needed to understand the reasons for vaccine failure.